Japońskie normy jurysdykcyjne – już reżim brukselski czy jeszcze common law? - Nowak, Marcin (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The author indicates some of the similarities between the Japanese norms on international jurisdiction and the norms of the Brussels Régime (particularly having in mind the Regulation Brussels Ibis). In the next step, an attempt is made to highlight those norms which have a clearly distinctive character, making it impossible to clearly categorize the norms of the Japanese Code of Civil Procedure on international jurisdiction either to the Brussels Régime, or the common law
Keywords: private international law; international jurisdiction; Japan